ALK inhibition in two emblematic cases of pediatric inflammatory myofibroblastic tumor: Efficacy and side effects. Issue 5 (29th January 2019) - Brivio, Erica; Zwaan, C. Michel
Abstract: There is an increasing interest for anaplastic lymphoma kinase (ALK) inhibitors in pediatric oncology for specific entities such as ALK‐driven inflammatory myofibroblastic tumor (IMT). IMT treatment can be challenging due to localization of the tumor and in rare cases of metastasis. When standard surgical treatment is not feasible, ALK inhibitors may play an important role, as recently reported for the first‐generation ALK inhibitors (crizotinib). However, data on the second‐generation ALK inhibitors are limited. We report two emblematic cases of IMT in pediatric patients, treated with the second‐generation ALK inhibitor ceritinib in the context of a clinical trial (NCT01742286).